Analyzing the Impact of ESG Disclosure on the Cost of Capital - Arbawa, Asrifa Rizki; Sutarti (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) disclosure on the cost of capital among energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. The research is grounded in stakeholder and legitimacy theories, emphasizing that transparent ESG practices enhance investor confidence and reduce perceived risk. Employing a quantitative approach with secondary data, the study utilizes panel data regression through STATA 17, with model selection based on the Chow and Lagrange Multiplier tests. The findings reveal that social disclosure significantly reduces the cost of capital, indicating that enhanced transparency in social responsibility strengthens stakeholder trust and financing efficiency. Conversely, environmental and governance disclosures exhibit statistically insignificant effects, suggesting that these dimensions require integration with broader sustainability strategies to yield measurable financial benefits. The study contributes to the growing discourse on sustainability finance in emerging markets by providing empirical evidence from Indonesia’s energy sector. The results underscore the importance for corporations and regulators to prioritize social disclosure while improving environmental and governance reporting standards aligned with international frameworks to enhance capital cost efficiency and long-term financial resilience